Evidence for the important role of inflammation in xenotransplantation - Juan Li; Hidetaka Hara; Yi Wang; Charles Esmon; David K. C. Cooper; Hayato Iwase (BMC, 2019)
Abstract There is increasing evidence of a sustained state of systemic inflammation after pig-to-nonhuman primate (NHP) xenotransplantation (that has been termed systemic inflammation in xenograft recipients [SIXR]). Increases in inflammatory markers, e.g., C-reactive protein, histones, serum amyloid A, D-dimer, cytokines, chemokines, and a decrease in free triiodothyronine, have been demonstrated in the recipient NHPs. The complex interactions between inflammation, coagulation, and the immune response are well-recognized, but the role of inflammation in xenograft recipients is not fully understood. The evidence suggests that inflammation can promote the activation of coagulation and the adaptive immune response, but the exact mechanisms remain uncertain. If prolonged xenograft survival is to be achieved, anti-inflammatory strategies (e.g., the administration of anti-inflammatory agents, and/or the generation of genetically-engineered organ-source pigs that are protected from the effect of inflammation) may be necessary to prevent, control, or negate the effect of the systemic inflammation that develops in xenograft recipients. This may allow for a reduction in the intensity of exogenous immunosuppressive therapy. If immunological tolerance to a xenograft is to be obtained, then control of inflammation may be essential.